Identifikasi Masalah Mengenai Serikat Kerja - Dalimunthe, Muhammad Farhan; Lubis, Richy Aufa; Azzahra, Zahira Fatimah; Sipahutar, Sri Juliani; Sunaryo, Sunaryo (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Trade unions/labor unions are an inherent right for workers/laborers to form or join a trade union in the company where they work without intervention or influence from any party. One of the problems in the union is the unilateral dismissal of one of the CNN Indonesia TV stations. The method used in this research is descriptive research method. The sampling technique used was probability sampling using the Slovin method and obtained 16 employees. Data uses an ordinal scale. Primary data through questionnaires. According to the results of this research, from 16 employees, the most common trade union problem experienced by most employees is that their basic salary was cut by 6 employees (37.5%) who experienced the same thing, followed by not being given leave permission for 6 employees (37.5%). .5%) and as many as 4 people (25%) were sent home for several days.